Pengaruh Pengelolaan Kearsipan Terhadap Efisiensi Kerja Pegawai Pada Dinas Kearsipan dan Perpustakaan Provinsi Gorontalo - A, Apriani; Aneta, Asna; Isa, Rusli (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to ascertain and analyze This study employed a quantitative method with simple regression analysis. The population for this study was 34 employees at the Office of Archives and Library of Gorontalo Province. Moreover, the sample consisted of the entire population using the saturation sampling method. Based on the results of hypothesis testing/partial t-test, which demonstrated that the calculated t-value exceeded the tabulated value (2,738 1,693), and the significance value (0,001) was lower than the alpha probability value (0,05). Based on this explanation, it can be concluded that the hypothesis of this study was accepted or Ho was rejected, and Ha was confirmed, indicating that, individually, the Archival Management variable had a positive and significant influence on Employee Work Efficiency at the Office of Archives and Library of Gorontalo Province. The magnitude of the influence of archival management on employee work efficiency at the Office of Archives and Library of Gorontalo Province was 30,4%, while the remaining 69,6% was influenced by factors such as; work desire, work abulity, and work skills in performing tasks.